Bibliometric analysis of research trends and characteristics of drug-induced gingival overgrowth - Zhang, Ruonan; Wu, Jie; Zhu, Junyi; Wang, Xiaoxiao; Song, Jiangyuan (Frontiers in Public Health, 2022)
Objectives: Drug-induced gingival overgrowth (DIGO) is a frequent adverse medication reaction that is generally caused by cyclosporine, phenytoin, and nifedipine, which belong to the category of immunosuppressants, anticonvulsants, and calcium channel blockers, respectively. This bibliometric analysis aims to depict the main citation characteristics and analyze the research trends in DIGO investigations. Methods: An exhaustive search was performed in the Scopus database to create the bibliometric list of DIGO in the syntax. Furthermore, the information related to the number of citations, drugs related to DIGO, study topic and design, authorship, publication year, journal, contributing institution, country of origin, and the department was extracted. Results: In total, 399 papers on DIGO were retrieved in this study. The total number of citations and that after the removal of self-citations were 7814 and 7314, respectively. The mean number of citations was 19.6 in a range of 0–608. The main paper types were articles (76.94%) and reviews (19.55%). A remarkable increasing trend in the number of citations has been observed since 1994. Cyclosporine (44.89%) is the most commonly used drug that shares a close relationship with DIGO, followed by phenytoin (18.22%), nifedipine (17.93%), and amlodipine (6.81%). The review (27.82%) type constituted the most widely used design in the DIGO studies. According to the top 20 keywords, the risk factors and pathogenesis of DIGO have been prominent topics of research works for several years. Conclusions: This bibliometric analysis will facilitate the understanding of researchers and clinicians, especially those at the beginning of their careers in periodontology on DIGO, by identifying landmark research and providing an overview of this field.